Perceived influence of urban green infrastructure on quality of life in Lagos Metropolis, Nigeria - Adedotun Dipeolu (Town and Regional Planning)
Quality of life (QoL) in urban areas is closely linked to the availability and quality of green infrastructure (GI), which provides essential ecosystem services that enhance well-being. As cities worldwide strive for environmental sustainability, urban green infrastructure (UGI) has become a key strategy for mitigating environmental degradation and improving urban liveability. While research has established the benefits of UGI in both developed and developing contexts, hardly anything is known about how residents’ perceptions of UGI quality influence their QoL, particularly in developing nations, including Nigeria. This study investigates how Lagos residents perceive the quality of existing UGI and its impact on their QoL. A survey of 1,560 residents, selected through multi-stage sampling, reveals that respondents generally view the current available UGI as insufficient relative to their expectations. Specifically, the inadequacy of well-maintained green spaces, limited leisure areas, and poorly equipped parks contribute to this negative perception. Findings from descriptive statistics and regression analysis highlight that well-equipped green spaces, urban parks, and relaxation areas are key determinants of QoL. This emphasises the need for targeted improvements in UGI to enhance urban living conditions not only in Lagos, but also in other developing cities facing similar challenges.